Glibenclamide attenuates 2, 5-hexanedione-induced neurotoxicity in the spinal cord of rats through mitigation of NLRP3 inflammasome activation, neuroinflammation and oxidative stress. (1st October 2020) - Hou, Liyan; Yang, Jie; Li, Sheng; Huang, Ruixue; Zhang, Dongdong; Zhao, Jie; Wang, Qingshan
Highlights: HD induces NLRP3 inflammasome activation in the spinal cord of rats. Inhibition of NLRP3 inflammasome by glibenclamide attenuates HD-induced neurotoxicity in rats. Glibenclamide suppresses HD-induced microglial proinflammatory activation and oxidative stress in rats. Abstract: Chronic exposure to n -hexane, a widely used solvent in industry, causes sensorimotor neuropathy, which is mainly mediated by its toxic metabolite, 2, 5-hexanedione (HD). However, the mechanisms remain unclear. This study is designed to investigate whether nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome is involved in HD-induced neurotoxicity. Results showed that HD intoxication significantly elevated NLRP3 expression, caspase-1 activation and interleukin-1β (IL-1β) maturation in the spinal cord of rats, indicating NLRP3 inflammasome activation. Glibenclamide, a sulfonylurea inhibitor of NLRP3 inflammasome, reduced HD-induced NLRP3 inflammasome activation, which was associated with mitigated gasdermin D (GSDMD) cleavage, neurofilament protein L (NF-L) reduction and demyelination as well as axon degeneration in the spinal cord of rats. Subsequently, we found that inhibition of NLRP3 inflammasome by glibenclamide suppressed microglial activation and M1 polarization and simultaneously recovered M2 polarization in HD-intoxicated rats. Furthermore, glibenclamide treatment reduced the contents of malondialdehyde (MDA) as well as elevated glutathione (GSH) levels and total-antioxidative capacity in the spinal cord of HD-intoxicated rats, indicating attenuated oxidative stress. Collectively, our findings suggested that NLRP3 inflammasome activation contributed to HD-induced neurotoxicity by enhancing microglial M1 polarization and oxidative damage. Inhibition of NLRP3 inflammasome by glibenclamide might a potential avenue to combat n -hexane-induced neuropathy.